Angiopoietin-2 and Survival in Peripheral Artery Disease Patients - Höbaus, Clemens; Pesau, Gerfried; Herz, Carsten Thilo; Wrba, Thomas; Koppensteiner, Renate; Schernthaner, Gerit-Holger (Thrombosis and Haemostasis, 2018)
Survival of peripheral arterial disease (PAD) patients increased over the last decade due to increased use of secondary preventive medication and rapid revascularization of PAD patients. Angiogenetic markers such as vascular endothelial growth factor (VEGF), angiopoietin-2 (Ang-2) and its receptor Tie-2 might be useful markers to assess the residual risk for mortality in PAD patients. The aim of this study was to evaluate angiogenetic markers for the prediction of mortality in a PAD cohort. For this purpose, 366 patients (mean age: 69 ± 10 years) with PAD Fontaine stage I or II were included and followed up over a 5-year study period. Serum Ang-2, Tie-2 and VEGF levels were measured by bead-based multiplex assay. All-cause mortality and major cardiovascular events (MACE) including all-cause death, non-fatal stroke and non-fatal myocardial infarction were analysed by Kaplan–Meier and Cox regression analyses after 5 years. Ang-2 was associated with Tie-2 (R = 0.151, p = 0.006) and VEGF levels (R = 0.160, p = 0.002). However, only Ang-2 was linked to all all-cause mortality in PAD patients (hazard ratio [HR]: 1.55 [1.23–2.15], p = 0.008) even after adjustment for age and gender, haemoglobin A1c, low-density lipoprotein cholesterol, systolic blood pressure and glomerular filtration rate (HR: 1.44 [1.03–2.00], p = 0.032). Furthermore, an association of Ang-2 and MACE in PAD patients (HR: 1.36 (1.03–1.78), p = 0.028) was found. This result implies that Ang-2 might be used as an additional marker to stratify PAD patients to predict poor mid-term life expectancy.
Keywords: angiopoietin-2; Tie-2; vascular endothelial growth factor; mortality; peripheral arterial disease; atherosclerosis